2019
DOI: 10.1177/0025802419858538
|View full text |Cite
|
Sign up to set email alerts
|

Management of DNA evidence collected on adolescents in sexual assault investigations: A 10-year review from a large Italian rape centre

Abstract: Little research is available on the actual forensic use of genetic analyses performed in sexual violence cases, despite their relevant role in legal processes. The present retrospective study aimed to contribute to filling this gap in research, evaluating the actual number of serological/DNA analyses that followed medical examination of female adolescent victims of sexual violence. The study was performed in a large rape centre in Milan (North Italy) by analysing all medical records of female victims of sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Probably, as a result of practice and cultural factors, Italian public prosecutors are accustomed to relying mostly on traditional pieces of evidence such as oral witnesses, presence of physical lesions, and wiretappings. 51 Similarly, we observed that magistrates or judges requested serological and/or DNA analyses in 86 out of 1211 (7,1%) cases of sexual violence against adult women. 52 …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Probably, as a result of practice and cultural factors, Italian public prosecutors are accustomed to relying mostly on traditional pieces of evidence such as oral witnesses, presence of physical lesions, and wiretappings. 51 Similarly, we observed that magistrates or judges requested serological and/or DNA analyses in 86 out of 1211 (7,1%) cases of sexual violence against adult women. 52 …”
Section: Discussionmentioning
confidence: 75%
“…This could be particularly important if one considers that, as described in our previous study, serological/DNA analyses were requested by the judicial authority in only 9/473 (1.9%) of cases of sexual violence among adolescents. 51 The cause of such infrequent use of genetic analysis in criminal proceedings regarding sexual violence in Italy is difficult to explain. Probably, as a result of practice and cultural factors, Italian public prosecutors are accustomed to relying mostly on traditional pieces of evidence such as oral witnesses, presence of physical lesions, and wiretappings.…”
Section: Discussionmentioning
confidence: 99%
“…The reported numbers, besides describing a cross-section of the phenomenon of violence in a society over the course of 1 year, have brought to light the current critical problems we have discussed. The issues do not end there, of course, because it would be necessary, for example, for the forensic samples taken to actually be stored and analyzed, which is not happening [ 33 ]. However, the introduction of forensic experts or at least skills into the EDs would be a major step forward.…”
Section: Discussionmentioning
confidence: 99%